Fungal metabolites: Nature’s key to antiangiogenic cancer therapies - Deepika, Seervi; Suma, Sarojini; Thea, Collinson; Krishnashish, Das; Rohini, Kizhakkethil (Plant Science Today, 2025)
Fungi have been thriving on planet Earth for millions of years, playing multiple roles in diverse ecosystems. Both free-living and endophytic fungi contain a plethora of secondary metabolites with rich bioactivity, which can be harnessed for therapeutic purposes. Many tumors grow rapidly due to the neovasculature formed by the activity of angiogenic genes. One of the strategies to curb such cancers is the use of anti-angiogenic drugs. Many fungi are treasure houses of chemicals such as fumagillin, barbatolic acid, usnic acid, trichodimerol and cordycepin. These can be utilized as anticancer drugs to reduce the neovascularization of tumors, thereby leading to the cessation of growth and the shrinkage of the tumor. This strategy could be significantly enhanced by using fungal nanoparticles synthesized through green methods, providing a more targeted treatment. By exploiting the unique properties of the tumor, these nanoparticles can offer more efficient means of delivering anticancer drugs directly to tumor sites, facilitating precise targeted therapy. This review emphasizes the significant potential of green-synthesised nanoparticles and fungal metabolites as novel molecules for targeted cancer therapy. Further research into their synergistic effects may lead to improved treatment outcomes and the development of more potent anti-angiogenic medications than those currently available.